Lồng ghép kiến thức văn hoá trong giờ học tiếng Nhật: Nghiên cứu tại Khoa Ngoại ngữ - Đại học Bách khoa Hà Nội - Trần Lan Phương, Trần Lan Phương (Tạp chí Giáo dục, 2026)
In the context of globalization and international integration, learning a foreign language does not stop at the ability to use language to communicate but also includes the ability to understand and adapt to cultural differences. In particular, for Japanese - a language closely associated with a specific culture, rich in symbols and implications - teaching separate from cultural factors will hardly help learners form truly effective communication skills. Therefore, integrating cultural knowledge into Japanese language classes is a necessary approach that helps enhance learning quality through the development of communicative competence. The article presents several approaches and types of cultural content incorporated into Japanese language teaching for students of the Faculty of Foreign Languages at Hanoi University of Science and Technology, analyzes the results of a survey on the current state of integrating cultural elements into lectures, pointing out limitations where cultural elements are still primarily considered supplementary, not specifically defined as learning objectives, and not closely linked to assessment mechanisms. Based on this, the author proposes several solutions for systematically integrating culture to improve training effectiveness.